Implementasi Pembelajaran Pendidikan Agama Islam di Fakultas Vokasi - Mahmudi, Mahmudi; Wahidah, Nina Ikhwati (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
The Religious Education course is one of the Personality Development Courses (MPK). Based on the 2006 Director General of Higher Education Decree, every university has the right to develop MPK signs according to their respective characteristics. Therefore, this paper wants to discuss the implementation of Islamic Religious Education learning at the Vocational Faculty of Nahdlatul Ulama University Lampung, which of course is a bit different from learning Islamic Religious Education in General Universities. The main objective of the Vocational Faculty is to prepare graduates who are ready to work and have high performance, therefore the lecturers of Islamic Education at the Faculty of Vocational Studies at Nahdlatul Ulama University, Lampung, try to bridge the gap between religious understanding and practice in the world of work, especially on the subject matter of "Work Ethic in Islam".